The Argentine financial sector: Performance, problems, and policy issues - Bernhard Fischer; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
This paper focusses on the development of the financial sector under conditions of high inflation. It begins with a description of the Argentine financial sector (Section II) and then reviews three distinct periods of financial policies since the early 1970s (Section III) . In the following chapter the main effects of financial repression are discussed and finally some policy suggestions for a restoration of the financial sector are presented.
Keywords: 330